Study on properties of carbon-coated silica prepared by polymer pyrolysis reinforced rubber composites - Xiaodong Gao; Weimin Yang; Chuansheng Wang; Xiaolong Tian (Polymer Testing, 2022)
Silica is an excellent reinforcing material and has been widely used in the rubber tire field. Silica can improve the wet grip performance and reduce rolling resistance. However, the application of silica in high-performance tires have been put forward with higher requirements due to the difficulties of dispersion, high heat generation, temperature sensitivity, and easy gel generation in the mixing process. To solve the above problems, nanocarbon-coated silica (silica@nanocarbon, SN) was proposed as a new reinforcing material in this paper. Nanocarbon coating prepared by pyrolysis of polyethylene. The hydroxyl groups on the surface of SN disappeared. Then, the new material was applied to the rubber composite, and the experimental results show that the curing time (t90) of the SN filled rubber compounds can be shortened. SN can improve the thermal conductivity of rubber compounds, and the compound has better dynamic mechanical properties. It also provides a feasible exploration for the application of modified silica in high-performance tires.